PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA MODEL INKUIRI TERBIMBING UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS SISWA SMP - Riris Susanti; Z. A. Imam Supardi; Sifak Indana (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research aimed to produce science learning materials that are feasible  to fascilitate students science process skill of junior high school. This research was conducted to implement the teaching and  learning materials based on guided inquiry model. This research developed them using Dick-Careys model and try outed using one group pre-test post-test design. The subjects of this research was science learning materials that consist of syllabus, lesson plan, students work sheet, instructional media, evaluation sheet to measure students science process skill. It was conducted to 28 eighth grade students in junior high school. The data were collected using validation, observation, test, and questionnaire. The data were analyzed  using descriptive quantitative and qualitative technique. The results  showed: (1) the teaching and learning materials developed are valid; (2) learning implementation got a good category; (3) the students participation  in actively learning; (4) students science process skill showed high category, (5) the students give positive response with very good category toward teaching and learning process. Based on this results, it can be concluded that the set of learning materials based on guided inquiry model have been developed are feasible to fascilitate  the students science process skill. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran IPA model inkuiri terbimbing yang layak untuk melatihkan keterampilan proses sains  siswa SMP. Penelitian ini merupakan penelitian pengembangan dengan model Dick-Carey dan desain uji coba penelitian menggunakan one group pre-test post-test design. Subyek penelitian adalah perangkat pembelajaran yang terdiri dari silabus, RPP, LKS, Buku Ajar Siswa, Instrumen Penilaian Keterampilan Proses Sains. Uji coba dilaksanakan pada siswa kelas VIII SMP sebanyak 28 siswa. Metode pengumpulan data menggunakan validasi, observasi, tes, dan pengisian angket. Teknik analisis data menggunakan deskriptif kuantitatif dan kualitatif. Hasil analisis data penelitian menunjukkan bahwa: (1) perangkat yang dikembangkan valid; (2) pembelajaran terlaksana dengan kategori baik; (3) siswa menjadi aktif dalam pembelajaran (4) keterampilan proses sains menunjukkan kategori tinggi (5) siswa memberikan respon positif dengan kategori sangat baik terhadap pembelajaran. Berdasarkan hasil penelitian di atas, dapat disimpulkan bahwa perangkat pembelajaran IPA model inkuiri terbimbing yang telah dikembangkan layak untuk melatihkan keterampilan proses sains siswa.